2022
DOI: 10.1111/ped.14910
|View full text |Cite
|
Sign up to set email alerts
|

Establishing norms on the Japanese version of the Eyberg Child Behavior Inventory

Abstract: Background The Eyberg Child Behavior Inventory (ECBI) is one of the standardized parent rating scales used to identify disruptive behavior problems in children in Western countries. This study aimed to determine norms for the Japanese version of the ECBI, including clinical cutoff scores among the general population in Japan. Methods This study established norms for the Japanese version of the ECBI using a sample of 1,992 parents of children aged 2–7, living in Japan. The research evaluates the validity and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The problem scale is measured using a twofactorial method ranging from "yes" (1 point) to "no" (0 points). We used the Japanese ECBI, 38,39 which Ito et al 40 confirmed to be reliable.…”
Section: Eyberg Children Behavior Inventory Japanese Version (Ecbi)mentioning
confidence: 99%
“…The problem scale is measured using a twofactorial method ranging from "yes" (1 point) to "no" (0 points). We used the Japanese ECBI, 38,39 which Ito et al 40 confirmed to be reliable.…”
Section: Eyberg Children Behavior Inventory Japanese Version (Ecbi)mentioning
confidence: 99%